1989
DOI: 10.1007/bf00399981
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of the Clostridium perfringens enterotoxin gene

Abstract: Several gene banks of Clostridium perfringens in E. coli were constructed. Using a mixture of synthetic 29-mer DNA probes clones were selected containing inserts from the C. perfringens gene coding for the enterotoxin. This has allowed sequencing of the complete gene and its flanking regions. The decuded amino acid sequence (320 a.a.) was found to differ at several sites from the sequence published previously by others. Two 40-mer DNA-probes were used to detect the toxin gene in C. perfringens strains isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 13 publications
1
49
2
Order By: Relevance
“…In the case of the intestinal contents of healthy pigs and swine feed, none of the 97 C. perfringens isolates tested in a previous study were positive for the enterotoxin gene (15). Using a cpe DIG probe, Tschirdewahn et al (34) reported that cpe ϩ strains were present in 14, 22, 10, and 0% of fecal isolates from horses, cattle, poultry, and pigs, respectively, while Van Damme-Jongsten et al (37) reported that only 6% of the 98 C. perfringens isolates they obtained from a variety of animals were cpe ϩ . There are few reports of the prevalence of cpe ϩ strains in nonoutbreak foods.…”
Section: Discussionmentioning
confidence: 92%
“…In the case of the intestinal contents of healthy pigs and swine feed, none of the 97 C. perfringens isolates tested in a previous study were positive for the enterotoxin gene (15). Using a cpe DIG probe, Tschirdewahn et al (34) reported that cpe ϩ strains were present in 14, 22, 10, and 0% of fecal isolates from horses, cattle, poultry, and pigs, respectively, while Van Damme-Jongsten et al (37) reported that only 6% of the 98 C. perfringens isolates they obtained from a variety of animals were cpe ϩ . There are few reports of the prevalence of cpe ϩ strains in nonoutbreak foods.…”
Section: Discussionmentioning
confidence: 92%
“…Enterotoxin gene-carrying (cpe-positive) C. perfringens type A is a common cause of food poisoning and is also involved in sporadic and antibiotic-associated diarrhea (19). Fewer than 5% of C. perfringens strains carry cpe (9,22).…”
mentioning
confidence: 99%
“…However, most of these isolates are nonenterotoxigenic strains. Recent surveys suggest that only about 6% of all C. perfringens isolates carry the gene (cpe) encoding enterotoxin (8,19). It therefore is necessary to distinguish the enterotoxigenic organisms from the nonenterotoxigenic ones to confirm food poisoning by C. perfringens.…”
mentioning
confidence: 99%